Thermodynamic properties of liquid alkali metals - Thakor, P.B.; Gajjar, P.N.; Jani, A.R. (Condensed Matter Physics, 2001)
The internal energy, entropy and Helmholtz free energy of liquid alkali metals,
viz. Na, K, Rb and Cs are investigated using pseudopotential perturbation
scheme based on Gibbs-Bogoliubov variational technique. A local
pseudopotential is applied to describe the electron-ion interaction in the
liquid alkali metals. To introduce the exchange and correlation effects, the
local field correction function proposed by Taylor is employed. The computed
values for internal energy, entropy and Helmholtz free energy for the
liquid alkali metals are in excellent agreement with the experimental data. Внутрішня енергія, ентропія та вільна енергія Гельмгольца рідких
лужних металів (Na, K, Rb і Cs) вивчається в рамках підходу збурених
псевдопотенціалів, що базується на варіаційній техніці Гіббса-Боголюбова. Для опису електрон-іонної взаємодії в рідких лужних металах застосовано локальний псевдопотенціал. Обмінні та кореляційні ефекти представлено з використанням запропонованої Тейлором
функції, що враховує поправку на локальне поле. Отримані значення внутрішньої енергії, ентропії та вільної енергії Гельмгольца для рідких лужних металів чудово узгоджуються з експериментальними даними.